TECHNOLOGICAL PROCESSES IN MANUFACTURING PRODUCTS FROM METAL: HISTORICAL CONTEXT AND WAYS OF RENAISSANCE - Варивончик, A. В.; Бондар, І. С.; Мазур, Б. М.; Швець, І. В. (Art and Design, 2021)
The aim of the work is to clarify the peculiarities of the development of Ukrainian art metal products in a historical context and to determine the ways of reviving artistic metalworking in the XXI century. Methodology. The research is based on culturological, historical and art history methods of analysis; applied historical-analytical, cultural-historical and the method of figurative-stylistic analysis of the means of artistic and decorative expressiveness of products. Results. The article examines the main stages in the development of technological processes in the execution of artistic metal products. The main techniques of artistic metal processing are analyzed: "lost wax", filigree, engraving, casting, forging, diffusion, electroplating, etc. The influence of external and internal factors in the development of artistic metal processing in Ukraine is studied. Identified the existing problems in the manufacture of art items from metal. Scientific novelty. The facts of the development of technologies for artistic metal processing in Ukraine are revealed and the ways of reviving the production of metal products as a type of decorative and applied art are determined. Practical significance. In the art of artistic metal processing, we highlight the issues of the revival and preservation of the industry in modern Ukraine through the study of technologies, traditions, the search for new forms, methods and techniques of working with materials.